Penguatan Civic Disposition Siswa melalui Program Wisata Edukasi Benteng Pancasila: Pendekatan Kuasi-Eksperimen One Group Pretest Posttest - Endrise Septina Rawanoko; Bramastia Bramastia; Leo Agung Sutimin; Triyanto Triyanto; Winarno Winarno; Deni Zein Tarsidi; Djono Djono; Andrea Salsalova (Medan Resource Center, 2025)
This study investigates the effectiveness of the Benteng Pancasila educational tourism program in strengthening students’ civic disposition amid concerns about declining engagement with national values in the era of globalization. The research addresses the central question of how educational tourism contributes to enhancing key civic qualities such as nationalism, tolerance, social concern, and civic participation. Employing a quasi-experimental One Group Pretest Posttest design supported by qualitative observations and interviews, the study provides both statistical and contextual insights. The results show a substantial improvement in students’ civic disposition, with the average score increasing from 3.06 in the pretest to 4.07 in the posttest, indicating a 32.9% gain. Qualitative evidence further reveals heightened emotional involvement, reflective thinking, and deeper understanding as students engaged with the learning environment. These findings demonstrate that educational tourism at Benteng Pancasila functions as an effective contextual learning strategy for cultivating national character and reinforcing the broader aims of Pancasila-based civic education.